OP0284 Mtor Plays A Decisive Role in the Rheumatoid Mesenchymal Tissue Response to Inflammation. (10th June 2014) - Karonitsch, T.; Dalwigk, K.; Holinka, J.; Sevelda, F.; Niederreiter, B.; Steiner, C.; Bilban, M.; Windhager, R.; Steiner, G.; Smolen, J.; Kiener, H.; Superti-Furga, G.
Abstract : Background: By integrating microenvironmental cues, mTOR has evolved as a critical determinant for the maintenance of cellular homeostasis and function. As such, the unfolding biology of mTOR revealed a crucial role in cancer, metabolic diseases and ageing. Now, accumulating evidence suggests that mTOR may also have an important modulatory function in the cellular response to inflammatory cues, such as TNF. Whether or not this also applies to fibroblast-like synoviocytes (FLS), particularly in the context of rheumatoid synovitis, remains elusive. Objectives: To evaluate the role of mTOR in the rheumatoid synovial tissue response to inflammation (TNF). Methods: A simplified 3-D model of the synovium was used to evaluate the significance of mTOR activity for the inflammatory mesencyhmal tissue response. FLS viability and proliferation was assessed by Annexin/7-AAD staining and a 3H-Thymidine incooperation assay, respectively. mTOR activity was blocked by Torin-1, which is a well known specific inhibitor of mTOR functions. In addition, RA-FLS (n=5) were exposed to TNF (6 hours) in the presence or absence of Torin-1 and the GeneChip® PrimeView array™ was used for gene expression profiling. Assessment of regulated genes was determined via SAM analysis. The expression of selected candidates was validated by Q-PCR and ELISA. To assess mTOR activity in RA-FLS, immunoblotting (IB) was performed using phosphospecific antibodies to TSC2, mTOR, AKT and S6K. Results: Stimulation of the 3D synovial organ cultures with TNF resulted in hyperplasia of the lining layer at the surface of the spheres. Strikingly, the mTOR inhibitor Torin-1 prevented TNF-induced FLS proliferation and lining layer hyperplasia. Importantly, Torin-1 alone or in combination with TNF did not affect RA-FLS viability. On the other side, gene expression profiling revealed that inhibition of mTOR results in the enhanced production of NFkB regulated (proinflammatory) genes, such as IL-6, IL8, or MMP1. Finally, immunoblotting of FLS lysates demonstrated that the mTOR pathway is activated by TNF, suggesting that the FLS response to inflammation (e.g. TNF) is controlled by a signalling cascade that involves mTOR. Conclusions: These studies provide insight into determinants of the synovial tissue response to inflammation and suggest a multifaceted regulatory role for mTOR in arthritis, especially in rheumatoid arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2843